PENGARUH BURNOUT DAN DISPOSISI MATEMATIS TERHADAP KEMAMPUAN BERPIKIR KRITIS SERTA DAMPAKNYA PADA KEMAMPUAN PEMECAHAN MASALAH - Putri Nacinta Yahya; Bambang Sri Anggoro; Dona Dinda Pratiwi; Adek Erni Kurnia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of students’ critical thinking and problem-solving abilities, which are influenced by internal factors such as burnout and mathematical disposition. The study aimed to analyze the effect of burnout and mathematical disposition on critical thinking skills and their impact on problem-solving abilities. This research employed a survey method with a causal approach. Data were collected using burnout questionnaires, mathematical disposition questionnaires, critical thinking tests, and problem-solving tests. The research sample consisted of students selected using a sampling technique adjusted to the research needs. The data were analyzed using path analysis to determine the direct effects among variables. The results showed that burnout had a significant effect on critical thinking skills and problem-solving abilities. Mathematical disposition also had a significant effect on critical thinking skills and problem-solving abilities. However, mathematical critical thinking skills did not have a significant effect on problem-solving abilities. These findings indicate that burnout and mathematical disposition are important factors influencing students’ critical thinking and problem-solving abilities. Therefore, learning strategies that reduce burnout and improve mathematical disposition are needed to support students in solving mathematical problems.